Analisis Tindak Pidana Dengan Sengaja Dan Rencana Terlebih Dahulu Menghilangkan Nyawa Orang Lain (Putusan Nomor 114/Pid.B/2022/PN-Mnd): Analisis Tindak Pidana Dengan Sengaja Dan Rencana Terlebih Dahulu Menghilangkan Nyawa Orang Lain (Putusan Nomor 114/Pid.B/2022/PN-Mnd) - Alexander Joshua Pratama; Setiyono (Faculty of Law, Universitas Trisakti, 2024)
Determining the criminal acts of murder, premeditated murder, and persecution resulting in the victim's death poses challenges due to subtle differences. The research questions are: Can the defendant's actions qualify as premeditated murder under Article 340 of the Criminal Code? What is the criminal liability for the accused in Decision Number 114/Pid.B/2022/PN.Mnd? This study adopts a normative legal research approach, employing descriptive analysis and literature studies. The research found that indicate that the defendant's actions meet the criteria for premeditated murder under Article 340. The defendant was sentenced to 11 years in prison, but this verdict is inadequate as the defendant fulfilled all three elements of planning to end a life. The conclusion is an ideal sentence would be a minimum of 20 years in accordance with Article 340 of the Criminal Code.